2020
DOI: 10.2147/ibpc.s277582
|View full text |Cite
|
Sign up to set email alerts
|

<p>Prevalence of Hypertension and Its Associated Factors Among Gimbi Town Residents, Ethiopia: A Community-Based Cross-Sectional Study</p>

Abstract: Background: Globally, sixty-two percent of cerebrovascular disease and forty-nine percent of ischemic heart disease are attributable to increased blood pressure. Half of the patients with stroke and heart disease were due to hypertension. Objective: This study aimed to identify prevalence of hypertension and its associated factors in Gimbi town, Ethiopia. Methods: We conducted a community-based cross-sectional study from May to June 2017 on 471 participants in Gimbi town, western Ethiopia. A systematic samplin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 21 publications
(49 reference statements)
1
5
0
Order By: Relevance
“…These figures were higher than those reported in the study done at Jimma University Specialized Hospital, where 26.4% were overweight and only one individual was obese (32). Body mass index was significantly associated with hypertension in the present study, and this was also replicated in other studies done in different regions of Ethiopia (23,25,26,27). Other studies in Sub-Saharan Africa (Angola and Kenya) have also demonstrated the presence of a significant association between overweight or obesity and hypertension (33,34).…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…These figures were higher than those reported in the study done at Jimma University Specialized Hospital, where 26.4% were overweight and only one individual was obese (32). Body mass index was significantly associated with hypertension in the present study, and this was also replicated in other studies done in different regions of Ethiopia (23,25,26,27). Other studies in Sub-Saharan Africa (Angola and Kenya) have also demonstrated the presence of a significant association between overweight or obesity and hypertension (33,34).…”
Section: Discussionsupporting
confidence: 78%
“…The prevalence of newly diagnosed HTN (36.2%) in the present study is higher than the overall prevalence of hypertension reported from the national NCDs STEPS survey among the Ethiopian adult population (15.8%) [20], community-based cross-sectional studies in Addis Ababa, central Ethiopia (29.2%) [21], and Dire Dawa city, eastern Ethiopia (24.43%) [22], and a cross-sectional study on public health facilities in Addis Ababa, central Ethiopia (32.3%) [23]. It was also much higher than the prevalence of newly diagnosed HTN reported from studies done in Debre Markos town, north-west Ethiopia (12.7%) [24], Durame town, southern Ethiopia (14%) [25], and Gimbi Town, western Ethiopia (24.8%) [26]. The higher prevalence of undiagnosed HTN in the current study as compared with that of the overall prevalence of HTN in the national NCDs STEPS survey may be explained by the increasing burden of the predisposing factors for HTN.…”
Section: Discussionmentioning
confidence: 79%
“…Patients with a family history of hypertension were more likely to be hypertensive compared to patients without a family history of hypertension. This is supported by a study in Gimbi, Ethiopia (19), southwest Ethiopia (6), a community-based study in Gondar, Ethiopia (13), and the Miyun district of Beijing, China (25). This could be because family members may share genetic factors and mostly exercise similar lifestyles.…”
Section: Discussionmentioning
confidence: 71%
“…In our study, patients aged >60 years were found to be with nearly two times higher chance of having hypertension compared to patients who were aged 18-40 years. This is supported by a systematic review and meta-analysis (7), a community-based study in Gondar, Ethiopia (13), Gimbi, Ethiopia (19), and a study among older adults in rural Ethiopia (18). This could be due to the biological effect of increased arterial resistance caused by arterial thickening and stiffness that occurs as one gets older (13,23).…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation